Meetings on Ky Boulevard (Dostoevsky vs Chernyshevsky) - Sitnikova, Vera (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2024)
This article examines some aspects of Dostoevsky’s polemic with Chernyshevsky reflected in the novel Crime and Punishment. Chernyshevsky’s philosophical concept, embodied in its most complete form in the novel What Is to Be Done?, was overshadowed by the authority of the author, who was subjected to repression. It attracted the generation formed in the era of radical changes by its simplicity, logic and seeming irrefutability. Dostoevsky’s novel became a “retort” in which it was subjected to a comprehensive verification of its truth. This critical attitude greatly influenced the artistic originality of Crime and Punishment. A modern Dostoevsky reader cannot help but notice the similarities with Chernyshevsky’s novel at the level of plot and key details, as well as direct references to stories about new people.